NON-VIOLENT ISLAMIC ELEMENTARY SCHOOL: CHILD-FRIENDLY SCHOOLS IN INCLUSIVE CLASSES DURING THE COVID PANDEMIC - Barokah, Sarah Mustika; Wangid, Muhammad Nur (UIN Sunan Kalijaga Yogyakarta, 2021)
The rise of child abuse cases in Indonesia has demanded the school to implement an anti-violence policy. Thus, the inclusion school of MI Amanah has implemented an anti-violence policy as an implementation form of the Child-Friendly School program. The objective of this research was to describe the implementation of the anti-violence policy during the learning process in the inclusion class as an embodiment of a child-friendly school in MI Amanah, Malang District. This research exerted a qualitative approach; the research data were collected through interviews, observation, and documentation; the data were then analyzed qualitatively and descriptively. The research location was at MI Amanah, Turen Sub-district, Malang District. The research was conducted from August to December 2020 by employing the foundation's president, principal, and teachers as the research subjects. The research finding indicated that implementing an anti-violence policy in student learning was covered in planning, implementation, and assessment. The learning planning was conducted by designing and organizing the learning materials without ignoring the child specificity; also allocating play, time, and rest. The learning implementation was to use polite greetings, put forward a psychological approach and positive discipline, make study groups in the inclusion class, care for students when they got through learning difficulties, raise tolerance environment, and provide worship and sleeping time. The learning assessment was done objectively by featuring authentic assessment; the assessment should be employed without comparing; the assessment regards the student's potential and skill.